Exploring The Role and Authority of Local Government in the Context of International Relations (Comparative Study between Ulsan City and Makassar City) - Darussalam, Miftah Farid; Safaat, Ayu Rezky; Agustin, Maya Madya (Journal of Paradiplomacy and City Networks, 2026)
The implementation of decentralization in developing countries generally goes hand in hand with the process of democratization. However, each country implements a decentralization system with varying levels of authority, which affects the role of local governments in conducting international cooperation. This study aims to compare the authority of local governments in conducting international cooperation between the City of Ulsan, South Korea, and the City of Makassar, Indonesia. Using a qualitative method through a comparative study approach supplemented by interviews, this study employs a decentralization framework as an instrument to measure the level of local government authority. The intensity of cooperation is used to identify the extent to which these authorities are implemented in foreign relations. The results of the comparison based on the constitutions of both countries show that local governments in South Korea have broader authority than city governments in Indonesia. This difference is reflected in the intensity of international cooperation, with Ulsan City recording a higher number of international cooperation initiatives than Makassar City.